Development of a digital three-dimensional rodentmodel for production of small laboratory animalphantoms; European Journal of Nuclear Medicine and Molecular Imaging; Vol. 48, suppl. 1 : European Association of Nuclear Medicine, EANM'21 - Miloichikova I. A. Irina Alekseevna; Bulavskaya A. A. Angelina Aleksandrovna; Cherepennikov Yu. M. Yuriy Mihaylovich; Gargioni E. Elisabetta; Grigorieva (Grigorjeva) A. A. Anna Anatoljevna; Stuchebrov S. G. Sergey Gennadevich; Wegner M. (2021, 2021)
Title screen